`Goalkeepers are players too`: key attributes coaches` look for in talented youth soccer goalkeepers - Lethole, L.; Kubayi, A.; Toriola, A.; Larkin, P.; Stone, J. A. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Objective Currently, there is a gap in knowledge on what the key goalkeeper attributes are during talent identification and selection in soccer. Hence, the objective was to investigate South African coaches` perceptions regarding key attributes of talented youth soccer goalkeepers.